Real-time measurement of protein-protein interactions at single-molecule resolution using a biological nanopore - Thakur, Avinash Kumar (Nat Biotechnol, 2018)
Single-molecule analyses of transient protein-protein interactions are enabled using an engineered biological nanopore.Protein-protein interactions (PPIs) are essential for many cellular processes. However, the transient nature of these PPIs is difficult to quantitate due to numerous limitations of available methods. We engineered a genetically-encoded sensor for real-time sampling of transient PPIs at single-molecule resolution. Our sensor comprises a truncated outer membrane protein pore, a flexible tether, a protein receptor and a peptide adapter. When a protein ligand present in solution binds to the receptor reversible capture and release events of the receptor can be measured as current transitions between two open substates of the pore. Importantly, the binding and release of the receptor by a protein ligand can be unambiguously discriminated in a complex sample containing fetal bovine serum. Our selective nanopore sensor could be applied for single-molecule protein detection, could form the basis for a nanoproteomics platform or might be adapted to build tools for protein profiling and biomarker discovery.